A carbon-neutral scenario simulation of an urban land–energy–water coupling system: A case study of Shenzhen, China. (10th January 2023) - Lin, Gang; Jiang, Dong; Yin, Yitong; Fu, Jingying
Abstract: As the core engine of the Guangdong–Hong Kong–Macao Greater Bay Area, Shenzhen plays a typical representative and leading role in the process of China's realization of the "double carbon" strategic goal, i.e., achieving peak carbon dioxide emissions by 2030 and carbon neutrality by 2060. Starting from an urban complex ecosystem, the aim of this study was to establish a system for an integrated urban land–energy–water system to achieve the "double carbon" objectives. Under a framework of urban land–energy–water integration, this study assessed the isomorphism of economy, population, water resources, energy, land use, and a carbon emission system and whether Shenzhen can achieve carbon neutralization in 2060 in a scenario of natural evolution. Then, it took carbon neutralization as the constraint, conducting backward reasoning to obtain values for the population, economic, technological development, water resources, energy consumption, and land carbon sequestration capacity of Shenzhen. Our study shows that the following: (1) Controlling water consumption synergistically reduces water-related energy consumption, while reducing energy consumption indirectly reduces water consumption by directly affecting energy-related water consumption, reflecting the transfer and feedback effect of the water–energy coupling relationship. (2) In the carbon neutral scenario, a rise in the forest cover increased 14, 000 tons of carbon sinkage and resulted in the additional consumption of 262, 700 cubic meters of ecological water. Therefore, the competition and coordination mechanism among the internal elements of the integrated urban land–energy–water system should be of high concern in the process of carbon neutralization. (3) In the future, carbon capture, utilization and storage technology and an increasing proportion of clean power will be the main ways to achieve carbon neutrality in Shenzhen. The purpose of this study was to clarify the current situation of carbon emissions and to put forward reference suggestions for the city to address a carbon neutralization strategy in the future. Highlights: The coupling relationship between land, water, energy and carbon are studied from a systematic perspective. Under the framework of urban land-energy-water system, the carbon neutralization path is simulated. Sustainable development approaches and response measures to achieve carbon neutrality.